A rubber composition for an anti-longitudinal-tear wear-resistant conveyor belt and a method for producing the same

CN122978552APending Publication Date: 2026-10-27SHANXI SHANLI BUNA RUBBER MASCH BELT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611486364.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

本发明主要用于解决现有技术中原纤化芳纶浆粕在高剪切混炼过程中易发生微纤丝损伤和再次团聚,且刚性芳纶浆粕与柔性橡胶基体之间缺少组成及模量逐步过渡的弹性界面,导致纤维裂纹桥联作用不足的问题

Benefits of technology

1.本发明将原纤化对位芳纶浆粕先与含极性基团的第一二烯弹性体复合,再使所得浆粕复合单元分散于第二二烯弹性体连续相中,可在浆粕主干纤维及微纤丝的至少部分表面形成极性弹性体附着区域,并使该附着区域与第二二烯弹性体连续相形成界面过渡,减少浆粕在后续混炼中的再次团聚以及微纤丝直接承受剪切所产生的损伤,并有利于载荷由橡胶基体向芳纶浆粕逐步传递。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978552A_ABST
    Figure CN122978552A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of rubber composition for conveyor belt, and discloses a rubber composition for anti-longitudinal-tearing wear-resistant conveyor belt and a preparation method thereof.The composition takes natural rubber and butadiene rubber as a matrix, and comprises reinforcing fillers, aramid pulp composite masterbatch, a vulcanization system and an antioxidant system.The aramid pulp composite masterbatch comprises fibrillated p-aramid pulp, a first diene elastomer containing a polar group attached to at least part of the surface of the aramid pulp, and a continuous phase of a second diene elastomer.The composition can further comprise a short aramid fiber composite masterbatch containing magnetically responsive short-cut p-aramid fibers.In the preparation process, the composite masterbatches are prepared first, then the butadiene rubber is premixed with the reinforcing fillers, and the composition is obtained through first-stage mixing, second-stage mixing with the addition of the fiber composite masterbatch at low temperature, and final mixing.The scheme is beneficial to maintaining the micro-fibril morphology of the pulp, improving the dispersion and interface transition of the fibers, and taking into account the longitudinal crack propagation resistance and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of rubber composition technology, specifically a rubber composition for longitudinal tear-resistant and abrasion-resistant conveyor belts and its preparation method. Background Technology

[0002] Conveyor belts are widely used in the continuous conveying of lumpy materials in mines, coal mines, metallurgy, cement plants, and ports. Their cover rubber directly withstands the impact, compression, scraping, and repeated bending of the materials. When sharp edges of ore or other sharp materials pierce the cover rubber, the initial cracks can easily propagate along the belt's running direction under the tension and periodic bending of the conveyor belt. Existing conveyor belt cover rubbers typically use natural rubber, butadiene rubber, or styrene-butadiene rubber as the base material, combined with carbon black, resin, vulcanizing agents, and antioxidants. Short fibers are added to improve the rubber compound's wear resistance and tear resistance. However, increasing the amount of carbon black and hard resin can limit the deformation capacity of crack tips, and ordinary short fibers may agglomerate or detach from the rubber interface in the compound, making it difficult to simultaneously maintain wear resistance and crack propagation resistance.

[0003] To address the aforementioned issues, CN109762212B discloses an ultra-wear-resistant conveyor belt. Its cover rubber comprises natural rubber, butadiene rubber, high-wear-resistant carbon black, and wear-resistant fibers composed of polyamide fibers and modified carbon fibers. The compatibility between the carbon fibers and rubber is improved through nitric acid treatment, acrylic system impregnation, and plasma treatment. CN105273208A discloses a method for preparing aramid pulp masterbatch. This method involves high-speed mixing of aramid pulp with a dispersant and adhesive resin, premixing with a rubber matrix, and then extruding and granulating the mixture using a twin-screw extruder to produce the masterbatch, thereby improving the dispersibility and reinforcing properties of the aramid pulp in the rubber.

[0004] The aforementioned technologies primarily improve fiber dispersion and interfacial adhesion through fiber surface activation, adhesive resin treatment, or pre-formulated masterbatch. However, they still lack synergistic control over the morphology maintenance and interfacial composition transition of fibrillated aramid pulp. When aramid pulp is directly mixed with carbon black under high temperature and high shear, its surface microfibrils are easily damaged, the length of the main fibers may decrease, and the dry pulp is prone to re-agglomeration. When a single rigid adhesive resin is used for treatment or when aramid pulp is directly contacted with non-polar diene rubber, interfacial regions with abrupt changes in polarity and modulus are easily formed between the rigid fibers and the flexible rubber. These two factors make the fibers prone to premature detachment, localized stress concentration, or direct fracture during crack propagation, making it difficult for them to stably perform their cross-crack load-bearing and progressive pull-out functions. Summary of the Invention

[0005] To overcome the shortcomings of existing technologies, this invention proposes a rubber composition for longitudinally tear-resistant and abrasion-resistant conveyor belts and its preparation method. This invention primarily addresses the problems in existing technologies where fibrillated aramid pulp is prone to microfiber damage and re-agglomeration during high-shear mixing, and where the rigid aramid pulp lacks an elastic interface with a gradual transition in composition and modulus between the rigid aramid pulp and the flexible rubber matrix, resulting in insufficient fiber crack bridging.

[0006] The technical solution adopted by the present invention to solve its technical problem is as follows: On the one hand, a rubber composition for longitudinal tear-resistant and wear-resistant conveyor belts is provided, which, based on 100 parts by weight of the base rubber, includes 40-58 parts by weight of reinforcing filler, 5-15 parts by weight of aramid pulp composite masterbatch, 1.2-2.2 parts by weight of sulfur, 1.0-2.5 parts by weight of accelerator, 3-7 parts by weight of activator, and 2-5 parts by weight of antioxidant; The base rubber is composed of 50-70 parts by weight of natural rubber and 30-50 parts by weight of butadiene rubber, wherein the sum of the parts by weight of natural rubber and butadiene rubber is 100 parts by weight. The aramid pulp composite masterbatch includes multiple pulp composite units and a second continuous phase composed of a second diene elastomer, wherein the multiple pulp composite units are dispersed in the second continuous phase; The pulp composite unit includes fibrillated para-aramid pulp and a first diene elastomer attached to at least a portion of the surface of the fibrillated para-aramid pulp. The fibrillated para-aramid pulp includes a main fiber and microfibrils extending from the surface of the main fiber. The first diene elastomer contains at least one polar group selected from carboxyl, epoxy, or anhydride groups. The second diene elastomer is natural rubber, polyisoprene rubber, or cis-butadiene rubber, and the molecular backbone of both the first and second diene elastomers contains carbon-carbon double bonds.

[0007] In this invention, "100 parts by mass of the base rubber" means that the sum of the mass parts of natural rubber and butadiene rubber, which are added separately as the base rubber, is 100 parts by mass. The diene elastomers serving as carriers, continuous phases, or attachment regions in the aramid pulp composite masterbatch and, optionally, the chopped aramid fiber composite masterbatch are all included in the mass of the corresponding composite masterbatch and are not counted repeatedly in the 100 parts by mass of the base rubber. When calculating the total amount of all elastomers in the final composition, the base rubber and the elastomers contained in each composite masterbatch are combined for calculation.

[0008] In a preferred embodiment, the total dry weight of the aramid pulp composite masterbatch is 100%, the fibrillated para-aramid pulp is 15%–30%, the first diene elastomer is 8%–25%, and the second diene elastomer is 45%–75%. All components are selected within the above ranges, and the sum of the mass percentages of all components in the masterbatch is 100%. The dry weight ratio of the first diene elastomer to the fibrillated para-aramid pulp is preferably 0.4:1–1.2:1, more preferably 0.6:1–0.9:1. When the aramid pulp composite masterbatch further includes a zinc source or a transition elastomer, the corresponding component is included in the total dry weight of the masterbatch, and the amount of the second diene elastomer is adjusted accordingly.

[0009] Based on 5-15 parts by weight of aramid pulp composite masterbatch, and calculated as 100 parts by weight of matrix rubber, the actual amount of fibrillated para-aramid pulp added is 0.75-4.5 parts by weight, preferably 1.0-3.0 parts by weight; the actual amount of the first diene elastomer added is 0.4-3.75 parts by weight. The above masterbatch composition and conversion relationship ensure that the amount of aramid pulp composite masterbatch added corresponds to the definite fiber component and interfacial elastomer component content.

[0010] The first diene elastomer is preferably used in the form of latex or a dispersion that can be stably dispersed in an aqueous phase. It can be selected from at least one of carboxylated nitrile rubber, carboxylated styrene-butadiene rubber, epoxidized natural rubber, maleic anhydride-grafted natural rubber, and maleic anhydride-grafted polybutadiene rubber, with carboxylated nitrile rubber being the most preferred. The carboxyl, epoxy, or anhydride groups give the first diene elastomer higher polarity relative to the second diene elastomer. The first diene elastomer also retains the diene backbone containing carbon-carbon double bonds to participate in subsequent vulcanization. When using different types of first diene elastomers, the amount of the first coagulant is adjusted according to its solid content and latex stability to form a filterable wet first pre-dispersion, with the coagulation endpoint being a clear supernatant.

[0011] The term "attached to at least a portion of the surface of the fibrillated para-aramid pulp" as used herein refers to the first diene elastomer aggregate remaining together with the fibrillated para-aramid pulp after flocculation with the first coagulant and washing with the aqueous phase, and located on a portion of the outer surface of the main fiber or microfibrils; the attachment does not require the formation of a uniform, completely continuous or closed coating layer.

[0012] The second diene elastomer is used to form a continuous carrier phase within the masterbatch particles before the aramid pulp composite masterbatch is added to the matrix rubber. The term "second continuous phase" as used herein refers to the second diene elastomer region that continuously extends within the masterbatch particles and surrounds multiple pulp composite units in the masterbatch state before the addition of the matrix rubber. During subsequent mixing and vulcanization, the second diene elastomer can interdiffused or partially fused with the matrix rubber, and it is not required to maintain an independent and distinguishable phase interface in the final vulcanized rubber. The second diene elastomer is preferably natural rubber or polyisoprene rubber; when using butadiene rubber, it is added in the form of butadiene rubber latex or an aqueous dispersion capable of co-coagulating with the wet first pre-dispersion, and the amount of the second coagulant is adjusted according to the solid content.

[0013] The reinforcing filler is preferably a granular rubber reinforcing filler, and more preferably, rubber-grade carbon black. The rubber-grade carbon black can be selected from at least one of N110, N220, N234, and N330 carbon black, and more preferably, N220 carbon black. Different grades of carbon black can be selected based on their iodine adsorption value and DBP absorption value. For reinforcing fillers requiring higher temperatures or higher shear for dispersion, it is preferable to pre-mix them in butadiene rubber before adding the aramid pulp composite masterbatch to reduce the shear force experienced by the fiber composite masterbatch during the reinforcing filler dispersion stage.

[0014] Furthermore, it also includes 2 to 10 parts by weight of chopped aramid fiber composite masterbatch; The chopped aramid fiber composite masterbatch includes chopped para-aramid fibers and a third continuous phase composed of a third diene elastomer, wherein the chopped para-aramid fibers are dispersed in the third continuous phase; The number-average length of the chopped para-aramid fibers is greater than the number-average length of the main fibers of the fibrillated para-aramid pulp, and the third diene elastomer is natural rubber, polyisoprene rubber, or cis-butadiene rubber.

[0015] Furthermore, the chopped para-aramid fibers include magnetically responsive chopped para-aramid fibers and non-magnetically responsive chopped para-aramid fibers; The magnetically responsive short-cut para-aramid fibers account for 20% to 50% of the total mass of the short-cut para-aramid fibers; Both the magnetically responsive chopped para-aramid fibers and the non-magnetically responsive chopped para-aramid fibers are dispersed in the third continuous phase, and the third diene elastomer is attached to at least a portion of the outer surface of the magnetically responsive chopped para-aramid fibers and the non-magnetically responsive chopped para-aramid fibers.

[0016] Furthermore, the magnetically responsive chopped para-aramid fiber includes a chopped para-aramid fiber core, a magnetically responsive elastomer layer attached to at least a portion of the outer surface of the chopped para-aramid fiber core, and an insulating elastomer layer covering at least a portion of the outer surface of the magnetically responsive elastomer layer. The magnetically responsive elastomer layer comprises carboxylated nitrile rubber and iron oxide particles dispersed in the carboxylated nitrile rubber; The isolation elastomer layer and the third continuous phase are composed of the same third diene elastomer, the isolation elastomer layer is located outside the magnetically responsive elastomer layer and is in contact with the third continuous phase.

[0017] Furthermore, the first diene elastomer is carboxylated nitrile rubber, and the second diene elastomer is natural rubber; The pulp composite unit also includes zinc carboxylate, which is formed by some of the carboxyl groups in the carboxylated acrylonitrile rubber and zinc ions, and is distributed together with the carboxylated acrylonitrile rubber on the outer surface of the fibrillated para-aramid pulp.

[0018] Furthermore, the aramid pulp composite masterbatch also includes non-carboxylated nitrile rubber, which is attached to at least part of the outer surface of the pulp composite unit containing the zinc carboxylate to form a transition elastomer region located between the carboxylated nitrile rubber and the second continuous phase, wherein the second continuous phase is in contact with the transition elastomer region. The mass content of acrylonitrile structural units in the non-carboxylated nitrile rubber is lower than that in the carboxylated nitrile rubber.

[0019] Furthermore, the second continuous phase of the aramid pulp composite masterbatch and the third continuous phase of the chopped aramid fiber composite masterbatch are both natural rubber, and the reinforcing filler is N220 carbon black.

[0020] On the other hand, a method for preparing a rubber composition for a longitudinally tear-resistant and abrasion-resistant conveyor belt is provided, comprising the following steps: S1. The fibrillated para-aramid pulp is dispersed in an aqueous phase, and a first diene elastomer latex is added for mixing. Then, a first coagulant is added for flocculation to obtain a wet first predispersant. The wet first predispersant is washed in an aqueous phase until the pH of the final wash is 6.5-7.0 and the conductivity is not higher than 800 μS / cm. The washed wet first predispersant is added to the second diene elastomer latex in the form of a wet slurry with a water content of 65%-75%. The total solid content of the system is adjusted to 8%-10%. The mixture is mixed at 200 r / min for 10 min. Then, a 3% (w / w) acetic acid aqueous solution is added as a second coagulant until the pH of the system is 4.8-5.2. The mixture is allowed to stand for 15 min to complete co-coagulation. The obtained co-coagulated material is dehydrated, dried, and granulated in sequence to obtain an aramid pulp composite masterbatch. S2. Select natural rubber, butadiene rubber, reinforcing filler, activator and antioxidant according to the composition and parameter requirements of the rubber composition. Perform a first premixing of the butadiene rubber and the reinforcing filler in the specified amount to obtain butadiene rubber reinforcing masterbatch. Perform a first stage mixing and discharge of the butadiene rubber reinforcing masterbatch, the natural rubber, the activator and the antioxidant. S3. After cooling the first-stage compound rubber and reducing its internal temperature to below 40°C, add the aramid pulp composite masterbatch for the second-stage compounding, and discharge the rubber at a discharge temperature not higher than 115°C. S4. After cooling the second-stage compound and reducing its internal temperature to below 40°C, sulfur and accelerator are added for final mixing to obtain the rubber composition for longitudinal tear-resistant and abrasion-resistant conveyor belts.

[0021] Furthermore, in preparing the chopped aramid fiber composite masterbatch comprising the magnetically responsive elastomer layer and the insulating elastomer layer, the chopped aramid fiber composite masterbatch is prepared according to the following process: Ferric oxide aqueous dispersion is mixed with carboxylated nitrile rubber latex to obtain magnetically responsive elastomer latex; a first portion of short-cut para-aramid fibers is dispersed in the magnetically responsive elastomer latex, and a third coagulant is added for flocculation to obtain a wet magnetically responsive fiber predispersant. The wet magnetically responsive fiber predispersant, the second part of chopped para-aramid fibers and the third diene elastomer latex are mixed, and a fourth coagulant is added to co-coagulate, so that the coagulated material of the third diene elastomer covers at least part of the outer surface of the magnetically responsive elastomer coagulated material in the wet magnetically responsive fiber predispersant and forms an isolating elastomer layer. The resulting coagulated material is dehydrated, dried and granulated in sequence to obtain a chopped aramid fiber composite masterbatch containing magnetically responsive chopped para-aramid fibers and non-magnetically responsive chopped para-aramid fibers. The first portion of chopped para-aramid fibers accounts for 20% to 50% of the total mass of the first portion of chopped para-aramid fibers and the second portion of chopped para-aramid fibers; In step S3, the aramid pulp composite masterbatch and the chopped aramid fiber composite masterbatch are added to the first-stage compounding rubber where the internal temperature is reduced to below 40°C for the second-stage compounding.

[0022] Furthermore, in an embodiment where the first diene elastomer is carboxylated nitrile rubber, the second diene elastomer is natural rubber, and the aramid pulp composite masterbatch also includes non-carboxylated nitrile rubber, in step S1, after the aqueous phase washing of the wet first predispersant is completed, zinc acetate aqueous solution, basic zinc carbonate aqueous dispersion, or active zinc oxide aqueous dispersion is added to the wet first predispersant to obtain a zinc-containing wet predispersant; The zinc-containing wet predispersant was mixed with non-carboxylated butadiene-acrylonitrile rubber latex, and a fifth coagulant was added for flocculation to obtain a wet transition layer composite. The wet transition layer composite is kept as a wet slurry with a water content of 65% to 75%, added to the natural rubber latex, and the total solid content of the system is adjusted to 8% to 10%. It is mixed at 200 r / min for 10 min, and then 3% acetic acid aqueous solution is added as the second coagulant until the pH of the system is 4.8 to 5.2. It is then allowed to stand for 15 min to complete co-coagulation. In step S2, the activator includes zinc oxide for vulcanization activation, and the zinc oxide for vulcanization activation is subjected to the first premixing together with the butadiene rubber and the reinforcing filler.

[0023] The beneficial effects of this invention are as follows: 1. The present invention first combines fibrillated para-aramid pulp with a first diene elastomer containing polar groups, and then disperses the resulting pulp composite unit in a continuous phase of a second diene elastomer. This can form polar elastomer attachment regions on at least a portion of the surface of the pulp backbone fibers and microfibrils, and make the attachment regions form an interface transition with the continuous phase of the second diene elastomer. This reduces the re-agglomeration of the pulp in subsequent mixing and the damage caused by the microfibrils being directly subjected to shearing, and facilitates the gradual transfer of load from the rubber matrix to the aramid pulp.

[0024] 2. In this invention, fibrillated para-aramid pulp and short-cut para-aramid fibers with a relatively large number average length are separately prepared into composite masterbatches and then introduced together into a rubber composition. This allows the fibrillated pulp to participate in the deflection and interfacial friction of smaller-scale cracks, while the short-cut fibers participate in the traversal load-bearing of larger-scale cracks. The two types of fibers share the load under different crack sizes, which is beneficial to balance the longitudinal crack propagation resistance and wear resistance of the conveyor belt cover rubber.

[0025] 3. In this invention, a magnetically responsive elastomer containing iron oxide particles is attached to at least a portion of the outer surface of a short-cut para-aramid fiber, and an insulating elastomer covers at least a portion of the outer surface of the magnetically responsive elastomer, thereby endowing the fiber with magnetically responsive properties and reducing the direct exposure of iron oxide particles to the rubber matrix interface. The insulating elastomer is in contact with the third continuous phase, which helps to maintain the dispersion state of the magnetically responsive short-cut fiber in the masterbatch and provides material conditions for adjusting fiber orientation using an external magnetic field during the conveyor belt forming process.

[0026] 4. The present invention, by setting zinc carboxylate in carboxylated nitrile rubber and attaching non-carboxylated nitrile rubber with a low content of acrylonitrile structural units to at least part of the outer surface of zinc-containing pulp composite units, forms a transitional elastomer region between the carboxylated nitrile rubber and the second continuous phase, which is beneficial to maintaining the load-bearing stability of the pulp surface layer and mitigating the polarity and modulus difference between the zinc-containing region and the second continuous phase.

[0027] 5. In the preparation process of this invention, butadiene rubber is first pre-mixed with reinforcing fillers, and then mixed with natural rubber in the first stage. After the internal temperature of the first-stage compound drops below 40°C, aramid pulp composite masterbatch and chopped aramid fiber composite masterbatch are added. The second stage of mixing is completed under the condition that the discharge temperature does not exceed 115°C. Subsequently, the second-stage compound is cooled to below 40°C for final mixing. In the scheme where natural rubber is used in the second and third continuous phases, this feeding sequence allows the reinforcing fillers to enter the matrix along with the butadiene rubber reinforcing masterbatch, and allows the fiber composite masterbatch to mix with the natural rubber matrix under lower temperature and shear conditions, reducing the damage of aramid fibers in the high temperature and high shear stages. This balances the contribution of reinforcing fillers to wear resistance and the inhibitory effect of aramid fibers on crack propagation. Attached Figure Description

[0028] The invention will now be further described with reference to the accompanying drawings.

[0029] Figure 1 This is a schematic diagram of the aramid pulp composite masterbatch structure in this invention; Figure 2 This is a schematic diagram of the short-cut aramid fiber composite masterbatch structure in this invention; Figure 3 This is a schematic diagram of a partial structure of the magnetically responsive short-cut para-aramid fiber in this invention; Figure 4 This is a schematic diagram showing the positional relationship between the masterbatch components and reinforcing fillers in the rubber composition of this invention; Figure 5 This is a flowchart of the preparation method in this invention; Figure 6 This is a SEM image of the protofibrillated para-aramid pulp in this invention; Figure 7 These are representative field-of-view comparison images of SEM cross-sections of Example 1 and the comparative example in this invention, mainly used to compare the voids at the fiber periphery interface. Figure 8 These are low-magnification fiber orientation identification images of the masterbatch sheets of Example 1 and Comparative Example 6 after being treated with the same magnetic field in this invention; Figure 9 This is a comparison diagram of longitudinal tear strength in this invention; Figure 10 This is a comparison chart of the volumetric wear of the rotating roller type in this invention; Figure 11 This is the dynamic crack propagation curve in this invention; Figure 12 These are fiber orientation angle distribution diagrams of Example 1 and Comparative Example 6 of the present invention after being treated with the same magnetic field.

[0030] Figure 1In the middle: 1. Second continuous phase; 2. Pulp composite unit; 3. Main fiber; 4. Microfiber; 5. First diene elastic coating layer; 6. Short-cut aramid fiber composite masterbatch; 7. Third continuous phase; 8. Non-magnetically responsive short-cut para-aramid fiber; 9. Magnetically responsive short-cut para-aramid fiber; 10. Short-cut para-aramid fiber; 11. Magnetically responsive elastomer layer; 12. Ferric oxide particles; 13. Isolating elastomer layer; 14. Natural rubber continuous phase; 15. Butadiene rubber dispersed phase; 16. Reinforcing filler; 17. Fiber contained in aramid pulp composite masterbatch; 18. Fiber contained in short-cut aramid fiber composite masterbatch. Detailed Implementation

[0031] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below in conjunction with specific embodiments.

[0032] like Figure 1 As shown, the aramid pulp composite masterbatch includes a plurality of pulp composite units dispersed in a second continuous phase. The pulp composite unit includes fibrillated para-aramid pulp and a first diene elastomer attached to at least a portion of its surface. The fibrillated para-aramid pulp has a main fiber and microfibrils extending from the surface of the main fiber.

[0033] like Figure 2 and Figure 3 As shown, the short-cut aramid fiber composite masterbatch contains both magnetically responsive short-cut para-aramid fibers and non-magnetically responsive short-cut para-aramid fibers. Figure 3 One type of magnetically responsive chopped fiber cross-sectional structure is shown, wherein a magnetically responsive elastomer is attached to at least a portion of the outer surface of the chopped para-aramid fiber core, iron oxide particles are dispersed in the magnetically responsive elastomer, and an isolation elastomer covers at least a portion of the outer surface of the magnetically responsive elastomer and is in contact with a third continuous phase.

[0034] like Figure 4 As shown, N220 carbon black enters the matrix rubber along with the cis-butadiene rubber reinforcing masterbatch, while aramid pulp composite masterbatch and chopped aramid fiber composite masterbatch respectively introduce the corresponding fibers into the matrix rubber; Figure 4 This is used to illustrate the positional relationship of each masterbatch component and reinforcing filler in the rubber composition, and is not used to define the continuous or dispersed phase morphology of the final vulcanized rubber.

[0035] The overall process of this invention for preparing aramid pulp composite masterbatch, chopped aramid fiber composite masterbatch, and performing staged mixing and final refining is as follows: Figure 5 As shown.

[0036] Raw material description: Unless otherwise stated, all weight parts below are based on dry matter, and the amounts of latex and aqueous dispersions are calculated based on measured solid content; deionized water is used in the aqueous phase dispersion, washing, and coagulation processes. All raw materials are commercially available products that meet the specifications listed in Table 1.

[0037] The scanning electron microscopy morphology of the fibrillated para-aramid pulp used is as follows: Figure 6 As shown, the main fibers and microfibers extending from the surface of the main fibers can be identified.

[0038] Table 1 Main Raw Materials and Specifications Preparation of composite masterbatch: 1. Preparation of aramid pulp composite masterbatch P-1. Based on dry basis, P-1 consists of 20.00% fibrillated para-aramid pulp, 15.00% carboxylated nitrile rubber, 0.45% active zinc oxide, 10.00% non-carboxylated nitrile rubber, and 54.55% natural rubber.

[0039] The fibrillated para-aramid pulp was added to deionized water to prepare a dispersion with a dry matter content of 1.0%. The dispersion was stirred for 15 min at 25–30 °C and 300 rpm. Carboxylated nitrile rubber latex was diluted with deionized water to a solid content of 10%, and added to the pulp dispersion while stirring at 300 rpm. Mixing was continued for 10 min. A 5% (w / w) calcium chloride aqueous solution was slowly added until the latex flocculated and the supernatant became clear. The mixture was filtered to obtain a wet first predispersant. The wet first predispersant was washed with deionized water until the pH of the final wash was 6.5–7.0 and the conductivity was not higher than 800 μS / cm.

[0040] An aqueous dispersion of active zinc oxide with a solid content of 30% was added to the washed wet first predispersant. The dry basis of the active zinc oxide was 0.45% of the total dry mass of P-1. The mixture was stirred at 50℃ and 200 r / min for 30 min to obtain a zinc-containing wet predispersant. Then, 10.00% of the total dry mass of P-1 (based on a dry basis) of non-carboxylated nitrile rubber latex was added and mixed for 10 min. Finally, a 5% (w / w) calcium chloride aqueous solution was added for flocculation to obtain a wet transition layer composite.

[0041] The wet transition layer composite was maintained as a wet slurry with a moisture content of 65%–75%, and added to natural rubber latex, so that the dry basis mass of natural rubber accounted for 54.55% of the total dry mass of P-1, and the total solid content of the system was adjusted to 8%–10%. The mixture was stirred at 200 r / min for 10 min, and a 3% (w / w) aqueous acetic acid solution was slowly added until the pH of the system was 4.8–5.2. The mixture was allowed to stand for 15 min to complete co-coagulation. The resulting co-coagulated material was dehydrated by pressure filtration and washed with deionized water, then dried under hot air at 60℃ until the moisture content was no higher than 1.0%. It was then granulated by low-temperature extrusion at an outlet temperature no higher than 90℃ to obtain P-1 with a particle size of 3–5 mm.

[0042] 2. Preparation of Aramid Pulp Composite Masterbatch P-2. P-2 comprises 20.00% fibrillated para-aramid pulp, 15.00% carboxylated nitrile rubber, and 65.00% natural rubber by dry weight percentage. Its preparation process is the same as P-1, except that: after washing the wet first pre-dispersion until the final wash solution pH is 6.5–7.0 and the conductivity is not higher than 800 μS / cm, the active zinc oxide aqueous dispersion and non-carboxylated nitrile rubber latex are not added. It is maintained as a wet slurry with a moisture content of 65%–75%, and directly added to the natural rubber latex. Co-coagulation is carried out according to the total solids content, mixing conditions, co-coagulation pH, and standing time described in P-1.

[0043] 3. Preparation of Aramid Pulp Composite Masterbatch P-3. P-3, by dry basis mass percentage, comprises 20.00% fibrillated para-aramid pulp, 15.00% carboxylated acrylonitrile rubber, and 65.00% synthetic polyisoprene rubber. Its preparation process is the same as P-2, except that natural rubber latex is replaced with synthetic polyisoprene latex.

[0044] 4. Preparation of Aramid Pulp Composite Masterbatch P-4. P-4, by dry basis mass percentage, comprises 20.00% fibrillated para-aramid pulp, 15.00% carboxylated acrylonitrile rubber, 1.20% zinc acetate dihydrate, 10.00% non-carboxylated acrylonitrile rubber, and 53.80% natural rubber. Its preparation process is the same as P-1, except that: the active zinc oxide aqueous dispersion is replaced with a 10% (w / w) aqueous solution of zinc acetate dihydrate; before adding the zinc acetate dihydrate aqueous solution, the pH of the wet first pre-dispersion slurry is adjusted to 7.0 ± 0.2, and mixed at 45℃ for 30 min.

[0045] 5. Preparation of short-cut aramid fiber composite masterbatches S-20, S-35, and S-50. All three masterbatches contain 30.00% short-cut para-aramid fibers; among them, magnetically responsive short-cut para-aramid fibers account for 20%, 35%, and 50% of the total mass of the short-cut para-aramid fibers, respectively. First, an aqueous dispersion of ferric oxide was mixed with carboxylated nitrile rubber latex, making the dry basis mass ratio of ferric oxide to carboxylated nitrile rubber 1:4. The mixture was dispersed at 600 r / min for 20 min to obtain a magnetically responsive elastomer latex.

[0046] Short-cut para-aramid fibers, serving as the first part of the magnetically responsive fiber core, were added to the magnetically responsive elastomer latex. The total solids content of the system was adjusted to 8%, and the mixture was stirred at 250 r / min for 10 min. A 5% (w / w) calcium chloride aqueous solution was slowly added for flocculation. After standing for 10 min, the mixture was filtered and washed with deionized water to obtain a wet magnetically responsive fiber predispersant. This wet magnetically responsive fiber predispersant, along with the second part of the non-magnetically responsive fiber, short-cut para-aramid fibers, and natural rubber latex, were mixed. The total solids content of the system was adjusted to 8%–10%, and the mixture was stirred at 200 r / min for 10 min. A 3% (w / w) acetic acid aqueous solution was added until the pH reached 4.8–5.2 to complete co-coagulation. The mixture was then treated according to the P-1 dehydration, washing, drying, and low-temperature granulation conditions. Thus, the aggregate of magnetically responsive elastomer latex adheres to at least a portion of the outer surface of the first portion of chopped para-aramid fibers, and the natural rubber co-aggregate further covers at least a portion of the outer surface of the magnetically responsive elastomer aggregate and the surface area of ​​the fibers not covered by it; a natural rubber layer is formed on the outer surface of the second portion of chopped para-aramid fibers.

[0047] Table 2. Dry base feeding ratio of composite masterbatch The zinc sources in P-1 and P-4 above are included in the mass of the corresponding aramid pulp composite masterbatch, but not in the mass fraction of the vulcanization activators listed in Table 3; the zinc oxide in Table 3 is used for the vulcanization activation of the rubber composition.

[0048] Table 3 Specific formulations of the examples Example 1: The rubber composition for longitudinal tear resistant and abrasion resistant conveyor belts was prepared according to the formulation of Example 1 listed in Table 3, and the specific steps are as follows.

[0049] S1. Prepare P-1 aramid pulp composite masterbatch and S-35 chopped aramid fiber composite masterbatch according to the aforementioned method, and place the two masterbatches in an environment of 23±2℃ and 50%±10% relative humidity for no less than 12h before mixing.

[0050] S2. The butadiene rubber reinforcing masterbatch and the first stage of mixing were carried out using an internal mixer. The raw materials were scaled up proportionally according to the mass proportions listed in Table 3, so that the filling factor of the internal mixer was 0.70. The initial temperature of the mixing chamber was set to 70℃ and the rotor speed to 60 r / min. 40 parts by mass of butadiene rubber were added and plasticized for 30 seconds; 24 parts by mass of N220 carbon black and 4 parts by mass of zinc oxide were added and mixed for 60 seconds; then the remaining 24 parts by mass of N220 carbon black were added and mixing continued until the total mixing time was 3.5 minutes and the rubber compound temperature reached 135±5℃. The rubber compound was then discharged to obtain the butadiene rubber reinforcing masterbatch.

[0051] The butadiene rubber reinforcing masterbatch was cooled at room temperature for at least 4 hours to reduce its internal temperature to below 40°C. The initial temperature of the mixing chamber was set to 70°C and the rotor speed to 55 r / min. The butadiene rubber reinforcing masterbatch and 60 parts by weight of natural rubber were added and mixed for 60 seconds. Then, 1.0 part by weight of stearic acid, 2.0 parts by weight of antioxidant 4020 and 1.0 part by weight of antioxidant RD were added, and mixing was continued for 180 seconds. When the temperature of the rubber compound reached 145±5°C, the compound was discharged to obtain the first-stage compound.

[0052] S3. Cool the first-stage compound for at least 4 hours and reduce its internal temperature to below 40°C. Set the initial temperature of the mixing chamber to 60°C and the rotor speed to 40 r / min. Add the first-stage compound and mix for 30 seconds. Divide 10 parts by mass of P-1 and 6 parts by mass of S-35 into two equal parts and add them alternately, with a 30-second interval between each addition. After all the materials are added, continue mixing for 60 seconds. Discharge the compound under the condition that the total mixing time of the second stage is 2.5 minutes and the discharge temperature is not higher than 115°C to obtain the second-stage compound.

[0053] S4. Cool the second-stage compound to below 40°C and pass it through a two-roll mill with a roll temperature of 50±5°C and a roll gap of 1.5mm three times. Add 1.6 parts by weight of insoluble sulfur, 1.4 parts by weight of accelerator CBS and 0.3 parts by weight of accelerator TMTD in sequence. After mixing for 5 minutes, adjust the roll gap to 4mm and sheet out. Let it stand at 23±2°C for 12 hours to obtain the rubber composition of Example 1.

[0054] To prepare vulcanized samples for subsequent testing, the rubber composition was calendered into a 6 mm thick sheet at 75±5℃, with the calendering direction as the longitudinal direction of the conveyor belt. The sheet was placed in a magnetic field region perpendicular to the calendering direction, with a magnetic induction intensity of 0.30±0.02T, and immediately fed into a flat vulcanizing machine after 30 seconds. The positive vulcanization time t90 was measured at 150℃ using a rotorless vulcanizer, and vulcanization was carried out at 150℃ and 10 MPa for t90+3 min.

[0055] The low-magnification fiber orientation identification results of the S-35 masterbatch sheets used in Example 1 and the S-C6 masterbatch sheets used in Comparative Example 6 after treatment with the same magnetic field are as follows: Figure 8 As shown. Figure 8 A representative field of view of 12 mm width and a scale bar of 2 mm are used. The linear structures in the figure represent the identifiable projections of chopped fibers in the film plane. Fibers crossing the field of view boundary only show the portion within the field of view, and the visible length of a single line segment in the figure is not used to replace the number-average length of the chopped fibers listed in Table 1. The chopped fibers in the S-35 film are more concentrated along the transverse direction of the film, while the chopped fibers in the S-C6 film are still close to random orientation.

[0056] Example 2: The difference from Example 1 is as follows: According to the formulation of Example 2 listed in Table 3, P-2 is used for the aramid pulp composite masterbatch, and S-20 is used for the chopped aramid fiber composite masterbatch; in step S2, 50 parts by weight of butadiene rubber, 45 parts by weight of N220 carbon black, and 3 parts by weight of zinc oxide are used to prepare a butadiene rubber reinforcing masterbatch, which is then mixed with 50 parts by weight of natural rubber, 1 part by weight of stearic acid, 3 parts by weight of antioxidant 4020, and 2 parts by weight of antioxidant RD in the first stage of compounding; in step S3, 15 parts by weight of P-2 and 2 parts by weight of S-20 are added; in step S4, 1.2 parts by weight of insoluble sulfur, 1.6 parts by weight of accelerator CBS, and 0.4 parts by weight of accelerator TMTD are added. The remaining preparation conditions, magnetic field treatment conditions, and vulcanization conditions are the same as in Example 1.

[0057] Example 3: The difference from Example 1 is as follows: According to the formulation of Example 3 listed in Table 3, P-4 is used for the aramid pulp composite masterbatch, and S-50 is used for the chopped aramid fiber composite masterbatch; in step S2, 30 parts by weight of butadiene rubber, 58 parts by weight of N220 carbon black, and 5 parts by weight of zinc oxide are used to prepare a butadiene rubber reinforcing masterbatch, wherein N220 carbon black is added in three equal portions, and then mixed with 70 parts by weight of natural rubber, 2 parts by weight of stearic acid, 1.5 parts by weight of antioxidant 4020, and 1 part by weight of antioxidant RD in the first stage of compounding; in step S3, 8 parts by weight of P-4 and 10 parts by weight of S-50 are added; in step S4, 2.0 parts by weight of insoluble sulfur, 1.0 parts by weight of accelerator CBS, and 0.2 parts by weight of accelerator TMTD are added. The remaining preparation conditions, magnetic field treatment conditions, and vulcanization conditions are the same as in Example 1.

[0058] Example 4: The difference from Example 1 is as follows: According to the formulation of Example 4 listed in Table 3, the aramid pulp composite masterbatch uses P-3, and no chopped aramid fiber composite masterbatch is added; in step S2, 35 parts by weight of butadiene rubber, 40 parts by weight of N220 carbon black, and 2.5 parts by weight of zinc oxide are used to prepare a butadiene rubber reinforcing masterbatch, which is then mixed with 65 parts by weight of natural rubber, 0.5 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, and 1 part by weight of antioxidant RD in the first stage of compounding; in step S3, 5 parts by weight of P-3 are added; in step S4, 2.2 parts by weight of insoluble sulfur, 2.0 parts by weight of accelerator CBS, and 0.5 parts by weight of accelerator TMTD are added. Since this example does not contain magnetically responsive chopped para-aramid fibers, the calendered sheet is not subjected to magnetic field treatment; the remaining preparation and vulcanization conditions are the same as in Example 1.

[0059] Comparative Example 1: The difference from Example 1 is that P-1 aramid pulp composite masterbatch is not prepared. Based on the dry basis composition corresponding to 10 parts by mass of P-1, 2.000 parts by mass of fibrillated para-aramid pulp, 1.500 parts by mass of carboxylated nitrile rubber obtained by separate coagulation and drying of carboxylated nitrile rubber latex, 0.045 parts by mass of active zinc oxide, 1.000 parts by mass of non-carboxylated nitrile rubber obtained by separate coagulation and drying of non-carboxylated nitrile rubber latex, and 5.455 parts by mass of natural rubber obtained by separate coagulation and drying of natural rubber latex; in the first stage of mixing in step S2, the above components are added together with natural rubber, butadiene rubber reinforcing masterbatch, activator, and antioxidant, wherein the fibrillated para-aramid pulp is added in a dry state and discharged with the first stage of mixing at 145±5℃; in step S3, only 6 parts by mass of S-35 chopped aramid fiber composite masterbatch are added. The total dry basis composition, magnetic field treatment conditions, and sulfidation conditions of each component are the same as in Example 1.

[0060] Comparative Example 2: The difference from Example 1 is that P-1 is replaced with a one-step co-coagulated aramid pulp masterbatch P-C2 with the same composition. P-C2 comprises, by dry weight percentage, 20.00% fibrillated para-aramid pulp, 15.00% carboxylated nitrile rubber, 0.45% active zinc oxide, 10.00% non-carboxylated nitrile rubber, and 54.55% natural rubber. In preparation, the fibrillated para-aramid pulp, carboxylated nitrile rubber latex, active zinc oxide aqueous dispersion, non-carboxylated nitrile rubber latex, and natural rubber latex are added to the aqueous phase at once and mixed at 300 r / min for 20 min. Then, a 5% (w / w) calcium chloride aqueous solution is added to coagulate the entire system. After washing, dehydration, drying at 60°C, and low-temperature granulation, P-C2 is obtained without washing and transferring the wet first pre-dispersion, zinc-containing treatment, transition layer flocculation, or second co-coagulation. In step S3, 10 parts by weight of P-C2 and 6 parts by weight of S-35 are added, and the remaining conditions are the same as in Example 1.

[0061] Comparative Example 3: The difference from Example 1 is that P-1 is replaced with aramid pulp composite masterbatch P-C3, which does not contain a zinc source. P-C3 comprises, by dry weight percentage, 20.00% fibrillated para-aramid pulp, 15.00% carboxylated nitrile rubber, 10.00% non-carboxylated nitrile rubber, and 55.00% natural rubber. Its preparation process is the same as P-1, but after washing the wet first pre-dispersion, the active zinc oxide aqueous dispersion is not added; instead, the non-carboxylated nitrile rubber latex is directly added to form the wet transition layer composite. In step S3, 10 parts by weight of P-C3 and 6 parts by weight of S-35 are added, and the remaining conditions are the same as in Example 1.

[0062] Comparative Example 4: The difference from Example 1 is that P-1 is replaced with aramid pulp composite masterbatch P-C4, which does not contain the non-carboxylated nitrile rubber transition elastomer region. P-C4 comprises, by dry weight percentage, 20.00% fibrillated para-aramid pulp, 15.00% carboxylated nitrile rubber, 0.45% active zinc oxide, and 64.55% natural rubber. Its preparation process is the same as P-1, but the zinc-containing wet pre-dispersion is not mixed with the non-carboxylated nitrile rubber latex; instead, it is directly added to the natural rubber latex in wet slurry form for co-coagulation. In step S3, 10 parts by weight of P-C4 and 6 parts by weight of S-35 are added, and the remaining conditions are the same as in Example 1.

[0063] Comparative Example 5: The difference from Example 1 is that S-35 is replaced with blank composite masterbatch S-C5, which does not contain chopped para-aramid fibers. S-C5 comprises 3.15% carboxylated acrylonitrile rubber, 0.79% iron oxide, and 96.06% natural rubber by dry weight percentage. In preparation, a fiber-free magnetically responsive elastomer latex is first prepared according to the conditions of S-35, then mixed with the natural rubber latex and co-coagulated, washed, dried, and granulated. In step S3, 10 parts by weight of P-1 and 6 parts by weight of S-C5 are added to maintain the total amount of masterbatch, as well as the amounts of iron oxide and carboxylated acrylonitrile rubber, similar to Example 1; the remaining conditions are the same as in Example 1.

[0064] Comparative Example 6: The difference from Example 1 is that S-35 is replaced with a composite masterbatch S-C6, in which none of the chopped aramid fibers have a magnetically responsive layer. The dry basis composition of S-C6 is the same as that of S-35. During preparation, all chopped para-aramid fibers are co-aggregated with natural rubber latex to form a non-magnetically responsive short-fiber masterbatch. Simultaneously, a ferric oxide aqueous dispersion and carboxylated nitrile rubber latex are separately aggregated to form fiber-free magnetically responsive elastomer particles. The two wet aggregates are then mixed, dehydrated, dried, and granulated to prevent ferric oxide and carboxylated nitrile rubber from adhering to the surface of the chopped para-aramid fibers. In step S3, 10 parts by weight of P-1 and 6 parts by weight of S-C6 are added, and the remaining conditions are the same as in Example 1.

[0065] Comparative Example 7: The difference from Example 1 is that S-35 is replaced with composite masterbatch S-C7, which does not have a natural rubber insulating elastomer layer on the outside of the magnetically responsive chopped para-aramid fibers. The dry basis composition of S-C7 is the same as that of S-35. In preparation, the first part of the chopped para-aramid fibers is first flocculated in a magnetically responsive elastomer latex formed by iron oxide and carboxylated nitrile rubber, washed, and then directly dried at 60°C to retain the magnetically responsive elastomer layer on its outer surface. The second part of the chopped para-aramid fibers is co-co-condensed and dried separately with all the natural rubber latex. Then, the resulting non-magnetically responsive short fiber masterbatch is mixed with the dried magnetically responsive chopped fibers at low temperature and granulated to prevent the natural rubber latex from co-condensing again outside the magnetically responsive elastomer layer. In step S3, 10 parts by weight of P-1 and 6 parts by weight of S-C7 are added, and the remaining conditions are the same as in Example 1.

[0066] Comparative Example 8: The difference from Example 1 is that the P-1 aramid pulp composite masterbatch and S-35 chopped aramid fiber composite masterbatch are not added after the first-stage compound has cooled, but are added to the internal mixer along with the second addition of N220 carbon black in step S2, and are mixed together with butadiene reinforcing masterbatch, natural rubber, activator, and antioxidant until the rubber compound temperature reaches 145±5℃, at which point the rubber is discharged; the low-temperature second-stage mixing in step S3 is omitted, and the resulting first-stage compound is directly subjected to final mixing after cooling. The formulation, magnetic field treatment conditions, and vulcanization conditions are the same as in Example 1.

[0067] Test Example 1: Tear Resistance, Abrasion Resistance and Tensile Properties Test Each group of rubber compositions was vulcanized according to the conditions of the corresponding examples or comparative examples, and then placed in an environment of 23±2℃ and 50%±10% relative humidity for 24 hours before sample preparation. Five parallel samples were taken for each test, and the data in Table 4 are expressed as mean ± standard deviation.

[0068] Longitudinal crack propagation resistance was determined using a trouser-shaped tear test. A strip specimen, 150 mm long, 30 mm wide, and 2.0 ± 0.2 mm thick, was cut along the rolling direction. Two clamping arms were formed by cutting 75 mm into the specimen's centerline from one end, aligning the crack propagation direction with the rolling direction. The specimen was stretched at 23 ± 2℃ with a clamping separation speed of 100 mm / min. The average tear force within the stable crack propagation range of 20–60 mm was taken, and this average tear force was divided by the specimen thickness to obtain the longitudinal crack propagation strength. Right-angle tear strength was determined using an uncut right-angled specimen with a thickness of 2.0 ± 0.2 mm at 500 mm / min.

[0069] Abrasion resistance was determined using a rotary roller abrasion tester. The sample diameter was 16.0 ± 0.2 mm, the vertical load was 10 N, P60 alumina sandpaper was used, and the abrasion distance was 40 m. The volumetric abrasion loss was calculated based on the mass difference before and after abrasion and the sample density; a smaller volumetric abrasion loss indicates better abrasion resistance. Tensile properties were measured using type 2 dumbbell-shaped samples, stretched to fracture at 500 mm / min, and the tensile strength was recorded. The test results are shown in Table 4.

[0070] A graphical comparison of longitudinal crack propagation intensity is shown below. Figure 9 A graphical comparison of the volumetric wear of rotating rollers is shown below. Figure 10 .

[0071] Table 4. Tear resistance, abrasion resistance, and tensile properties of the examples and comparative examples. As shown in Table 4, Examples 1-3 maintained high levels in longitudinal crack propagation strength, right-angle tear strength, and tensile strength. Example 3 exhibited lower volumetric wear due to its higher amount of reinforcing filler, while Example 1 showed a more balanced result between longitudinal crack propagation resistance and abrasion resistance. Example 4, which did not contain chopped aramid fiber composite masterbatch, had a lower longitudinal crack propagation strength than Examples 1-3. This indicates that the fibrillated aramid pulp can provide crack deflection and interfacial friction, while the longer chopped aramid fibers further participate in crack crossing load bearing.

[0072] In Comparative Example 1, the dry pulp was directly subjected to shear during the first stage of high-temperature mixing. In Comparative Example 2, all components were co-aggregated in one step. The tear resistance and abrasion resistance data of both were lower than those of Example 1, indicating that wet-state stepwise compounding and subsequent low-temperature addition are beneficial for preserving the pulp morphology and reducing agglomeration. Comparative Examples 3 and 4 lacked the zinc-containing structure or non-carboxylated nitrile rubber transition elastomer region, respectively, and their longitudinal crack propagation strength decreased. Comparative Examples 6 and 7 show that the spatial bonding relationship between the magnetically responsive elastomer and the fiber, as well as the external isolation elastomer, affect the orientation and load-bearing state of the chopped fibers during molding and vulcanization. In Comparative Example 8, the two types of fiber masterbatch were added to the high-temperature mixing stage in advance, and their overall performance decreased, corresponding to the test results of fiber morphology damage and local agglomeration.

[0073] Test Example 2: Dynamic Longitudinal Crack Propagation Test A vulcanized rubber strip measuring 150 mm in length, 25 mm in width, and 6.0 ± 0.2 mm in thickness was cut along the calendering direction. An initial 2.0 mm long notch was prepared at the center of the sample width, ensuring that the subsequent expansion direction of the notch tip was aligned with the calendering direction. The sample was mounted on a reciprocating flexure device and subjected to cyclic flexing at 23 ± 2℃, a flexure frequency of 5 Hz, and a maximum displacement of 57 mm. The flexures were then subjected to 1 × 10⁻⁶ cycles. 4 Times, 3×10 4 The sum of 5 × 10 4 After each cycle, the equipment was stopped, and the length from the notch tip to the crack front edge was measured using a reading microscope. Six specimens were tested in each group, and the average crack growth was taken. The results are shown in Table 5.

[0074] The dynamic crack propagation curves plotted based on the number of cycles and crack propagation length are shown below. Figure 11 .

[0075] Table 5. Dynamic longitudinal crack growth in the examples and comparative examples. As shown in Table 5, Example 1 exhibited relatively small crack growth rates at each flexure cycle stage, while Examples 2 and 3 also maintained low crack growth rates. The microfibers on the surface of the fibrillated aramid pulp can form multiple dispersed friction and deflection regions near the crack tip, while the longer chopped fibers bear the cross-crack load as the crack continues to propagate. Therefore, Examples 1-3 were able to limit crack growth even at higher cycle counts.

[0076] The larger crack growth in Comparative Examples 1, 2, and 8 is related to dry pulp agglomeration, stepwise compounding, insufficient interfacial transition structure, or premature entry of the fiber masterbatch into the high-temperature, high-shear stage. The results of Comparative Examples 3 and 4 indicate that both the zinc-containing region and the outer transition elastomer region affect interfacial stability under cyclic loading. Comparative Example 5, lacking longer chopped aramid fibers, experienced accelerated crack growth with increasing cycle count. Although Comparative Examples 6 and 7 still contained chopped fibers, the magnetically responsive elastomer was not attached to the fiber surface or lacked an insulating elastomer, resulting in higher crack growth than in Example 1.

[0077] Test Example 3: Aramid Fiber Dispersion, Morphology Retention, and Interface Morphology Test Samples were cut along the calendering direction from the second-stage compound or the corresponding pre-final compound of each group. After cooling in liquid nitrogen for 10 minutes, the samples were frozen and sectioned, with a section thickness of 80–100 μm. Ten fields of view were randomly selected for each sample under 100x optical microscopy. The number of pulp agglomerates with an equivalent diameter of not less than 100 μm was counted using image analysis software, and the length of continuously identifiable pulp backbone fibers in the section plane was measured. At least 200 backbone fibers were counted for each group.

[0078] Another vulcanized sample from the same location was subjected to liquid nitrogen brittle fracture, and the microfibers on the surface of the pulp backbone were observed under a scanning electron microscope at 2000x magnification. Using the number of identifiable microfibers per 100μm backbone length of unmixed fibrillated para-aramid pulp at the same magnification as 100%, the microfiber retention index for each group was calculated. The dark voids around the fibers in the brittle fracture surface were thresholded, and the proportion of the interface void area to the total area of ​​the fiber and its surrounding 20μm region within 20 random fields of view was statistically analyzed. The results are shown in Table 6.

[0079] Microscopic morphology of fibrillated para-aramid pulp is shown below Figure 6 A comparison of representative fields of view of cross-section SEM between Example 1 and Comparative Example 4 is shown in the figure. Figure 7 . Figure 7 Used to display the morphology of local interface voids around the fiber periphery, the number of pulp agglomerates is not quantitatively characterized by the number of fiber bundles in a single field of view; the number of pulp agglomerates is based on the multi-field statistical results listed in Table 6.

[0080] Table 6. Fiber morphology and interface morphology of Example 1 and comparative examples. As shown in Table 6, the pulp of Example 1 had fewer agglomerates, higher identifiable trunk length and microfiber retention index, and lower interfacial void area fraction. In Comparative Example 1, the dry pulp directly underwent the first stage of mixing, while in Comparative Example 8, both types of fiber masterbatch were added to the high-temperature mixing stage in advance. Both examples showed a shortening of the identifiable trunk length, a decrease in the microfiber retention index, and an increase in the number of agglomerates. Although Comparative Example 2 maintained the aqueous co-coagulation mode, it did not form a stepwise composite and interfacial transition structure, and its number of agglomerates and interfacial voids were still higher than those of Example 1.

[0081] Comparative Example 3, without a zinc source, maintained a pulp morphology similar to Example 1, but with an increased interfacial void area fraction. Comparative Example 4 lacked a non-carboxylated nitrile rubber transition elastomer region; its pulp agglomerate count was 2.2 / mm², close to 1.8 / mm² in Example 1, while the interfacial void area fraction increased from 1.9% to 4.2%. In the figure, the fiber-matrix interface of Comparative Example 1 showed tight bonding and smaller voids around the fiber periphery, while the morphology of Comparative Example 4, with larger local voids around the fiber periphery, corresponds to the interfacial void statistics in Table 6, indicating that a gradually changing elastic transition is still needed between the inner region containing the zinc carboxylate and the continuous phase of the second diene elastomer. The pulp morphology in Comparative Examples 5 and 6 were similar to that of Example 1; their macroscopic tear resistance differences mainly stemmed from the absence of chopped fibers or the lack of magnetically responsive elastomer attachment to the chopped fiber surface. In Comparative Example 7, the outer side of the magnetically responsive elastomer lacked an isolating elastomer, resulting in an increased void area fraction around the fiber periphery.

[0082] Test Example 4: Zinc-containing structure, magnetic response, and short-cut fiber orientation test The aramid pulp composite masterbatch used in each group was vacuum dried at 60℃ for 12 hours and then pulverized at low temperature. The samples were then tested using an attenuated total reflectance Fourier transform infrared spectrometer with a scanning range of 4000–600 cm⁻¹. -1 The resolution is 4cm. -1 A total of 32 scans were performed. The scan depth was 1580–1610 cm. -1 The asymmetric stretching vibration peak of carboxylates within the range of 2220–2250 cm⁻¹ -1 Baseline correction and integration were performed on the nitrile peaks within the range, and the area of ​​the carboxylate peak was divided by the area of ​​the nitrile peak as the characteristic peak area ratio of zinc carboxylate.

[0083] Approximately 50 mg of each group of vulcanized samples were taken, and the hysteresis curves were measured at room temperature using a vibrating sample magnetometer with an applied magnetic field range of ±800 kA / m. The saturation magnetization intensity when the magnetization intensity in the high-field region tended to stabilize was read. Separately, 100 μm thick slices were prepared along the film thickness direction, and at least 10 fields of view were collected under a polarizing microscope. The acute angles between at least 150 chopped aramid fibers and the transverse direction of the film were measured, and the average value of the square of the cosine of each angle was taken as the transverse orientation factor. A transverse orientation factor close to 0.5 indicates near-two-dimensional random orientation; an increasing value indicates a higher degree of fiber orientation along the transverse direction of the film. The results are shown in Table 7.

[0084] To verify the spatial binding relationship between magnetic particles and chopped fibers, S-35 chopped aramid fiber composite masterbatch used in Example 1 and S-C6 composite masterbatch used in Comparative Example 6 were subjected to liquid nitrogen brittle fracture. After carbon spraying on the sample surface, the chopped fibers were identified under scanning electron microscopy with an accelerating voltage of 10 kV and a working distance of 10 ± 1 mm. Energy dispersive X-ray spectroscopy was used to acquire Fe Kα elemental surface scans, with a single field-of-view acquisition time of 60 s. The Fe signal threshold was set by adding three times the standard deviation to the average Fe count in the region without obvious particles in the same field of view. The threshold-segmented Fe signal map was then registered with the fiber profile map. At least 100 identifiable chopped fibers were randomly selected from each group. When the overlap area between the Fe signal and the fiber profile reached more than 30% of the corresponding fiber projection area, it was recorded as a positive Fe co-localization signal on the fiber surface. S-35 and S-C6 were calendered into thin films with a thickness of 0.30±0.05 mm at 75±5℃ and fixed on a rigid frame with crosshair reference marks. The fiber orientation before the magnetic field was applied was recorded under a transmission light microscope. Then, a magnetic field with a magnetic induction intensity of 0.30±0.02 T and a direction consistent with the transverse direction of the film was applied for 30 s, and the same field of view was recorded again. To facilitate the simultaneous display of fiber length and orientation within a large field of view, a low-magnification field of view with a width of 12 mm was selected, and the image was subjected to background homogenization and fiber centerline extraction. Figure 8 The medium scale bar is 2mm, and the line segments shown represent the planar projection of the fiber. Fibers crossing the field of view boundary are only shown within the field of view. The images before and after magnetic field processing were translated and rotated and registered using the reference marks. At least 10 fields of view were acquired for each group, and at least 150 short-cut fibers were counted. The lateral orientation factor before and after magnetic field processing was calculated. The results are shown in Table 8.

[0085] The low-magnification fiber orientation identification results of the S-35 masterbatch sheets used in Example 1 and the S-C6 masterbatch sheets used in Comparative Example 6 after treatment with the same magnetic field are shown in the figure. Figure 8 The fiber orientation angle distribution of the two sets of thin films after being treated with the same magnetic field is shown in the figure. Figure 12 .

[0086] Table 7. Zinc-containing structures, magnetic responses, and orientation results of Example 1 and some comparative examples. Note: "—" indicates that the corresponding sample does not contain statistically oriented short-cut para-aramid fibers.

[0087] As shown in Table 7, Comparative Example 3 did not add a zinc source to the wet first pre-dispersion, and its zinc carboxylate characteristic peak area was relatively low. Both Example 1 and Comparative Example 4 formed a high carboxylate characteristic peak area ratio, but the interfacial voids and crack propagation data of Comparative Example 4 were still poor. This indicates that the role of the non-carboxylated nitrile rubber transition elastomer region is not only to form a zinc-containing structure, but also to regulate the interfacial transition between the zinc-containing inner region and the second continuous phase.

[0088] The saturation magnetization of Example 1 and Comparative Example 6 are similar, indicating that the total amount of magnetic phase they contain is similar. However, the transverse orientation factor of Example 1 is higher than that of Comparative Example 6, indicating that the overall magnetic response of the rubber composition is not equivalent to the ability of chopped aramid fibers to accept magnetic field torque. Although Comparative Example 7 still has a magnetic response, its transverse orientation factor is reduced and accompanied by a higher interfacial void area fraction because the same isolating elastomer as the third continuous phase is not provided on the outside of the magnetically responsive elastomer. Comparative Example 8, which adds chopped fiber masterbatch during the high-temperature mixing stage, also has a lower transverse orientation factor than Example 1, corresponding to the decrease in fiber length and local aggregation.

[0089] Table 8. Fe co-localization and orientation results on fiber surfaces before and after magnetic field treatment in Example 1 and Comparative Example 6 Table 8 shows that the Fe co-localization positivity rate on the fiber surface in the S-35 masterbatch used in Example 1 was 34%, which corresponds to the formulation ratio of 35% of the total chopped fibers in S-35 with magnetic response chopped fibers. In Comparative Example 6, only a small number of fibers in the S-C6 masterbatch reached the co-localization threshold due to accidental adjacency with independent magnetic response elastomer particles. Before magnetic field treatment, the lateral orientation factors of both groups of sheets were close to the level of two-dimensional random orientation. After the same magnetic field treatment, the lateral orientation factor of the S-35 sheet increased from 0.52 to 0.76, while that of the S-C6 sheet only changed from 0.51 to 0.52. This result indicates that when the overall magnetic phase content is similar, the adhesion of Fe3O4 and carboxylated nitrile rubber to at least part of the outer surface of the chopped fibers is beneficial for transferring the magnetic field effect to the fibers. This result is consistent with Table 7 and... Figure 8 , Figure 12 The orientation differences shown correspond to those shown.

[0090] The embodiments of the present invention have been described above with reference to the accompanying drawings. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the spirit and scope of the claims. All of these forms are within the protection scope of the present invention.

Claims

1. A rubber composition for longitudinally tear-resistant and abrasion-resistant conveyor belts, characterized in that, Based on 100 parts by weight of the base rubber, it includes 40-58 parts by weight of reinforcing filler, 5-15 parts by weight of aramid pulp composite masterbatch, 1.2-2.2 parts by weight of sulfur, 1.0-2.5 parts by weight of accelerator, 3-7 parts by weight of activator and 2-5 parts by weight of antioxidant; The base rubber is composed of 50-70 parts by weight of natural rubber and 30-50 parts by weight of butadiene rubber, wherein the sum of the parts by weight of natural rubber and butadiene rubber is 100 parts by weight. The aramid pulp composite masterbatch includes multiple pulp composite units and a second continuous phase composed of a second diene elastomer, wherein the multiple pulp composite units are dispersed in the second continuous phase; The pulp composite unit includes fibrillated para-aramid pulp and a first diene elastomer attached to at least a portion of the surface of the fibrillated para-aramid pulp. The fibrillated para-aramid pulp includes a main fiber and microfibrils extending from the surface of the main fiber. The first diene elastomer contains at least one polar group selected from carboxyl, epoxy, or anhydride groups. The second diene elastomer is natural rubber, polyisoprene rubber, or cis-butadiene rubber, and the molecular backbone of both the first and second diene elastomers contains carbon-carbon double bonds.

2. The rubber composition for longitudinal tear-resistant and abrasion-resistant conveyor belts according to claim 1, characterized in that, It also includes 2 to 10 parts by weight of chopped aramid fiber composite masterbatch; The chopped aramid fiber composite masterbatch includes chopped para-aramid fibers and a third continuous phase composed of a third diene elastomer, wherein the chopped para-aramid fibers are dispersed in the third continuous phase; The number-average length of the chopped para-aramid fibers is greater than the number-average length of the main fibers of the fibrillated para-aramid pulp, and the third diene elastomer is natural rubber, polyisoprene rubber, or cis-butadiene rubber.

3. The rubber composition for longitudinal tear-resistant and abrasion-resistant conveyor belts according to claim 2, characterized in that, The chopped para-aramid fibers include magnetically responsive chopped para-aramid fibers and non-magnetically responsive chopped para-aramid fibers; The magnetically responsive short-cut para-aramid fibers account for 20% to 50% of the total mass of the short-cut para-aramid fibers; Both the magnetically responsive chopped para-aramid fibers and the non-magnetically responsive chopped para-aramid fibers are dispersed in the third continuous phase, and the third diene elastomer is attached to at least a portion of the outer surface of the magnetically responsive chopped para-aramid fibers and the non-magnetically responsive chopped para-aramid fibers.

4. The rubber composition for longitudinal tear-resistant and abrasion-resistant conveyor belts according to claim 3, characterized in that, The magnetically responsive chopped para-aramid fiber includes a chopped para-aramid fiber core, a magnetically responsive elastomer layer attached to at least a portion of the outer surface of the chopped para-aramid fiber core, and an insulating elastomer layer covering at least a portion of the outer surface of the magnetically responsive elastomer layer. The magnetically responsive elastomer layer comprises carboxylated nitrile rubber and iron oxide particles dispersed in the carboxylated nitrile rubber; The isolation elastomer layer and the third continuous phase are composed of the same third diene elastomer, the isolation elastomer layer is located outside the magnetically responsive elastomer layer and is in contact with the third continuous phase.

5. The rubber composition for longitudinal tear-resistant and abrasion-resistant conveyor belts according to claim 1, characterized in that, The first diene elastomer is carboxylated nitrile rubber, and the second diene elastomer is natural rubber; The pulp composite unit also includes zinc carboxylate, which is formed by some of the carboxyl groups in the carboxylated acrylonitrile rubber and zinc ions, and is distributed together with the carboxylated acrylonitrile rubber on the outer surface of the fibrillated para-aramid pulp.

6. The rubber composition for longitudinal tear-resistant and abrasion-resistant conveyor belts according to claim 5, characterized in that, The aramid pulp composite masterbatch also includes non-carboxylated nitrile rubber, which is attached to at least part of the outer surface of the pulp composite unit containing the zinc carboxylate to form a transition elastomer region located between the carboxylated nitrile rubber and the second continuous phase, wherein the second continuous phase is in contact with the transition elastomer region. The mass content of acrylonitrile structural units in the non-carboxylated nitrile rubber is lower than that in the carboxylated nitrile rubber.

7. The rubber composition for longitudinal tear-resistant and abrasion-resistant conveyor belts according to claim 2, characterized in that, The second continuous phase of the aramid pulp composite masterbatch and the third continuous phase of the chopped aramid fiber composite masterbatch are both natural rubber, and the reinforcing filler is N220 carbon black.

8. A method for preparing a rubber composition for longitudinal tear-resistant and abrasion-resistant conveyor belts, applicable to the rubber composition described in any one of claims 1-7; characterized in that, Includes the following steps: S1. The fibrillated para-aramid pulp is dispersed in an aqueous phase, and a first diene elastomer latex is added for mixing. Then, a first coagulant is added for flocculation to obtain a wet first predispersant. The wet first predispersant is washed in an aqueous phase until the pH of the final wash is 6.5-7.0 and the conductivity is not higher than 800 μS / cm. The washed wet first predispersant is added to the second diene elastomer latex in the form of a wet slurry with a water content of 65%-75%. The total solid content of the system is adjusted to 8%-10%. The mixture is mixed at 200 r / min for 10 min. Then, a 3% (w / w) acetic acid aqueous solution is added as a second coagulant until the pH of the system is 4.8-5.

2. The mixture is allowed to stand for 15 min to complete co-coagulation. The obtained co-coagulated material is dehydrated, dried, and granulated in sequence to obtain an aramid pulp composite masterbatch. S2. Select natural rubber, butadiene rubber, reinforcing filler, activator and antioxidant according to the composition and parameter requirements of the rubber composition. Perform a first premixing of the butadiene rubber and the reinforcing filler in the specified amount to obtain butadiene rubber reinforcing masterbatch. Perform a first stage mixing and discharge of the butadiene rubber reinforcing masterbatch, the natural rubber, the activator and the antioxidant. S3. After cooling the first-stage compound rubber and reducing its internal temperature to below 40°C, add the aramid pulp composite masterbatch for the second-stage compounding, and discharge the rubber at a discharge temperature not higher than 115°C. S4. After cooling the second-stage compound and reducing its internal temperature to below 40°C, sulfur and accelerator are added for final mixing to obtain the rubber composition for longitudinal tear-resistant and abrasion-resistant conveyor belts.

9. The preparation method according to claim 8, characterized in that, The method also includes the step of preparing a short-cut aramid fiber composite masterbatch, which is prepared according to the following process: Ferric oxide aqueous dispersion is mixed with carboxylated nitrile rubber latex to obtain magnetically responsive elastomer latex; a first portion of short-cut para-aramid fibers is dispersed in the magnetically responsive elastomer latex, and a third coagulant is added for flocculation to obtain a wet magnetically responsive fiber predispersant. The wet magnetically responsive fiber predispersant, the second part of chopped para-aramid fibers and the third diene elastomer latex are mixed, and a fourth coagulant is added to co-coagulate, so that the coagulated material of the third diene elastomer covers at least part of the outer surface of the magnetically responsive elastomer coagulated material in the wet magnetically responsive fiber predispersant and forms an isolating elastomer layer. The resulting coagulated material is dehydrated, dried and granulated in sequence to obtain a chopped aramid fiber composite masterbatch containing magnetically responsive chopped para-aramid fibers and non-magnetically responsive chopped para-aramid fibers. The first portion of chopped para-aramid fibers accounts for 20% to 50% of the total mass of the first portion of chopped para-aramid fibers and the second portion of chopped para-aramid fibers; In step S3, the aramid pulp composite masterbatch and the chopped aramid fiber composite masterbatch are added to the first-stage compounding rubber where the internal temperature is reduced to below 40°C for the second-stage compounding.

10. The preparation method according to claim 8, characterized in that, The first diene elastomer latex is a carboxylated butadiene nitrile rubber latex, and the second diene elastomer latex is a natural rubber latex; in step S1, after the aqueous phase washing of the wet first predispersant is completed, zinc acetate aqueous solution, basic zinc carbonate aqueous dispersion or active zinc oxide aqueous dispersion is added to the wet first predispersant to obtain a zinc-containing wet predispersant. The zinc-containing wet predispersant was mixed with non-carboxylated butadiene-acrylonitrile rubber latex, and a fifth coagulant was added for flocculation to obtain a wet transition layer composite. The wet transition layer composite is kept as a wet slurry with a water content of 65% to 75%, added to the natural rubber latex, and the total solid content of the system is adjusted to 8% to 10%. It is mixed at 200 r / min for 10 min, and then 3% acetic acid aqueous solution is added as the second coagulant until the pH of the system is 4.8 to 5.

2. It is then allowed to stand for 15 min to complete co-coagulation. In step S2, the activator includes zinc oxide for vulcanization activation, and the zinc oxide for vulcanization activation is subjected to the first premixing together with the butadiene rubber and the reinforcing filler.

Citation Information

Patent Citations

  • Aramid pulp masterbatch preparation method

    CN105273208A

  • A super wear-resistant conveyor belt and its manufacturing process

    CN109762212B